Peran Generative Artificial Intelligence dalam Meningkatkan Efisiensi Proses Pembelajaran di Tingkat Tinggi - Wincent Wisely; Aurich Thedis; Roy Roy; Alkaffy Kaffy Ramba; Evander Banjarnahor (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2026)
The development of Generative Artificial Intelligence (Gen AI) has significantly transformed the learning process, particularly in improving task completion efficiency. This study aims to analyze the effect of Gen AI usage on learning efficiency among high school students and university students. A quantitative approach was employed using a survey of 83 respondents. The variables examined include frequency of use, duration of use, and learning efficiency, which is measured based on task completion time. The results indicate that the level of Gen AI usage is relatively high, with a mean frequency of 3.51 and a mean duration of 3.53, while efficiency shows the highest mean value of 3.94. Regression analysis reveals that the model is statistically significant (p-value < 0.05) with a coefficient of determination of , indicating that 61.18% of the variance in learning efficiency is explained by the model. Partially, frequency of use has a positive and significant effect on efficiency ( ; p-value < 0.05), whereas duration of use is not statistically significant ( ; p-value > 0.05). These findings suggest that usage intensity plays a more critical role than usage duration. Overall, Gen AI is shown to enhance learning efficiency; however, its effectiveness depends on how users actively and appropriately engage with the technology.